Year of the griffin - Jones, Diana Wynne (New York : HarperTrophy, 2001)
Elda, the griffin daughter of the great Wizard Derk, arrives for schooling at the Wizards' University where she encounters new friends, pirates, assassins, worry, sabotage, bloodshed, and magic misused.
"A Greenwillow book."
Sequel to: Dark Lord of Derkholm.
Booklist starred
School Library Journal
Wilson's Junior High School
Young Adult.
Keywords: Fantasy; Griffins -- Fiction; Magic -- Fiction; Schools -- Fiction; Griffins -- Fiction; Magic -- Fiction; School stories; Fantastic fiction